EDUCAÇÃO DO SER-MOTRÍCIO E A PRÁXIS CRIADORA - SANTOS, SÉRGIO OLIVEIRA DOS (2016)
The research starts from the Portuguese philosopher Manuel Sérgio work, investigating the implications and resonances in educational horizons from the comprehension of “ser-motrício”. The basics research questions are: How to experience, understand and interpret the human being in his motrician nature? What is his true way of being in action, overcoming the lonely physical look, considering the experience of life, language and human complexity? Which outspreads, resonances and educational implications may arise by these comprehensions and interpretations? Understanding this projection, we studied the “ser-motrício” in its ontological roots subsidized by the life experience, interpretation and human appreciation. In the educational dimension, it was considered that the “ser-motrício”, who feels, thinks, apprehends, incorporates, wishes, interacts, wonders, expresses and potencializes all of this condition in the connection of his experience of life with multiple languages, has received a comprehensive and more influenced treatment by the paradigm of simplicity and reductionism that, somehow, resonate in fragmented educational practices. To overcome this reductionism, we defend the creative praxis as authentic dimension of “ser-motrício”, in a project called "Appreciation of Human Motricity," a constructive